The Multi-Dimensional Influence of a Sports Activity on the Process of Psycho-Social Rehabilitation and the Improvement in the Quality of Life of Persons with Physical Disabilities - Niedbalski, Jakub (Qualitative Sociology Review, 2018)
Purpose: The purpose of the research is to analyze the role that sport plays in the lives of persons with physical disabilities within the process of rehabilitation and the improvement of their quality of life. Background: The article raises the notions of changes that take place in the life of a physically handicapped person which is due to their engagement in a sports activity. In the article, I refer to the subjective perspective of those researched, rendering their own point of view into the major subject of analysis. Methods: Qualitative data are exploited in the research, collected through a technique of unstructured interviews and undisguised observations conducted among the disabled practicing sports. Findings: The role of sport practiced by the disabled has been determined within several contexts, which were distinguished within the course of the research as analytical categories. Conclusion: On the basis of the research it was found that getting involved in a sports activity is significant within the process of experiencing life satisfaction, personal development and the reconstruction of the ego, self-identity, and transformations in the manner of perceiving both themselves and others. Therefore, a sports activity of a disabled person supports the rehabilitation process effectively.